Effect of baseline HbA1c level on the development of diabetes by lifestyle intervention in primary healthcare settings: insights from subanalysis of the Japan Diabetes Prevention Program. Issue 1 (24th April 2014) - Sakane, Naoki; Sato, Juichi; Tsushita, Kazuyo; Tsujii, Satoru; Kotani, Kazuhiko; Tominaga, Makoto; Kawazu, Shoji; Sato, Yuzo; Usui, Takeshi; Kamae, Isao; Yoshida, Toshihide; Kiyohara, Yutaka; et al.
Abstract : Objectives: To determine the effects of a lifestyle intervention on the development of type 2 diabetes mellitus (T2DM) among participants with impaired glucose tolerance (IGT), in particular in the subgroup with baseline glycated hemoglobin (HbA1c) levels ≥5.7%, in primary healthcare settings. Design: Randomized controlled trial. Setting: 32 healthcare centers in Japan. Participants: Participants with IGT, aged 30–60 years, were randomly assigned to either an intensive lifestyle intervention group (ILG) or a usual care group (UCG). Interventions: During the initial 6 months, participants in the ILG received four group sessions on healthy lifestyles by public health providers. An individual session was further conducted biannually during the 3 years. Participants in the UCG received usual care such as one group session on healthy lifestyles. Outcome measures: The primary endpoint was the development of T2DM based on an oral glucose tolerance test. Results: The mean follow-up period was 2.3 years. The annual incidence of T2DM were 2.7 and 5.1/100 person-years of follow-up in the ILG (n=145) and UCG (n=149), respectively. The cumulative incidence of T2DM was significantly lower in the ILG than in the UCG among participants with HbA1c levels ≥5.7% (log-rank=3.52, p=0.06; Breslow=4.05, p=0.04; Tarone-Ware=3.79, p=0.05), while this was not found among participants with HbA1c levels <5.7%. Conclusions: Intensive lifestyle intervention in primary healthcare setting is effective in preventing the development of T2DM in IGT participants with HbA1c levels ≥5.7%, relative to those with HbA1c levels <5.7%. Trial registration number: UMIN000003136.